Antioxidant Activity and Nutraceutical Potential of Selected Nepalese Wild Edible Fruits - Bhusal, Santoshi; Pant, Deepak Raj; Joshi, Giri Prasad; Adhikari, Minu; Raut, Jay Kant; Pandey, Manish Raj; Bhatt, Lok Ranjan (Scientific World, 2020)
Wild edible fruits play an important role in the nutrition of rural people especially in the hilly and mountainous region, where the wild fruits could be the only source to consume. Though wild edible fruits are widely utilized throughout the country, little works have been done in Nepal on their nutritional and phytochemical analysis. The main objective of this study was to evaluate the antioxidant activity and nutraceutical potential of the selected wild edible fruits. The fruit samples were extracted in appropriate solvents and all the analyses were done in triplicates using 96 well ELISA plate reader. Nutritionally, Rubus acuminatus was found to be rich in Vitamin C (0.78 ± 0.01 mg/g) over other fruits. Protein content was found to be high in Berberis napaulensis (2.26 ± 0.71 %) and R. ellipticus showed greater lipid (0.15 ± 0.01 %) and β-carotene content (1.08 ± 0.01 mg/100mg). R. acuminatus was found to have high flavonoid content (9.26 ± 0.40 mg QE/g) and exhibited higher antioxidant activity while B. angulosa (29.67 ± 2.28 mg GAE/g) had the highest phenolic content.